NAVOIY KON-METALLURGIYA KOMBINATI - Kosnazarov, S.T.; Jumamuratov, R.E.; Artikov, M.B.; Ko’chkinov, D.K. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of the role of the metallurgical industry in the world economy, the principles of development, methods of reproduction and the volume of minerals.